2010
DOI: 10.1128/aem.02685-09
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Enteric Viruses, Pathogen Indicators, and Salmonella Bacteria in Class B Anaerobically Digested Biosolids by Culture and Molecular Methods

Abstract: The most common class B biosolids in the United States are generated by mesophilic anaerobic digestion (MAD), and MAD biosolids have been used for land application. However, the pathogen levels in MAD biosolids are still unclear, especially with respect to enteric viruses. In this study, we determined the occurrence and the quantitative levels of enteric viruses and indicators in 12 MAD biosolid samples and of Salmonella enterica in 6 MAD biosolid samples. Three dewatered biosolid samples were also included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 42 publications
(52 reference statements)
4
76
0
6
Order By: Relevance
“…108(1): 77-83, February 2013 Wastewater treatment plants (WWTPs) generate large amounts of residual sludge as part of the sewage treatment process. This sludge contains a series of concentrated contaminants, mainly heavy metals and pathogenic microorganisms, such as bacteria, viruses, protozoa and helminths (Monpoeho et al 2004, Guzmán et al 2007, Viau & Peccia 2009, Wong et al 2010.…”
mentioning
confidence: 99%
“…108(1): 77-83, February 2013 Wastewater treatment plants (WWTPs) generate large amounts of residual sludge as part of the sewage treatment process. This sludge contains a series of concentrated contaminants, mainly heavy metals and pathogenic microorganisms, such as bacteria, viruses, protozoa and helminths (Monpoeho et al 2004, Guzmán et al 2007, Viau & Peccia 2009, Wong et al 2010.…”
mentioning
confidence: 99%
“…There was an average 4.2 log 10 (range 1.9 to 5.0 log 10 ) reduction in infectious virus in sludge after treatment in a study of five WWTPs (Simmons and Xagoraraki, 2011b). Wong et al (2010) and Monpoeho et al (2001) reported an average of 4 log 10 MPN/gm in class B sludge after dewatering (four WWTPs) or MAD (thirteen WWTPs). Differences in recovery levels after dewatering and some of the variation in the number of enterovirus positive samples between the two reports may have been due to differences in plant location and virological tests used.…”
Section: Biosolidsmentioning
confidence: 99%
“…Mesophilic anaerobic degradation is the most common method for generating Class B biosolids in the US (Wong et al, 2010). Land and agricultural use of class B sludge has been regulated by the US EPA to reduce pathogen transmission "by allowing time for natural processes to further reduce pathogen levels".…”
Section: Biosolidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimum separation distance of 0.75 m between the soil surface and groundwater is required when biosolids are applied. There are many regional variations in required set-back distances and other management practices to protect the environment and public health [118][119][120][121][122].…”
Section: Best Management Practices For Biosolids To Protect Water Quamentioning
confidence: 99%